Obstacles to the Application of Electronic Weigh in Motion Tickets - Aida Dewi; Vicki Dwi Purnomo (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2023)
Vehicle load measurement tools can be carried out dynamically without the need to stop the vehicle first with the Weigh In Motion system. This writing aims to find out exactly what is related to the Electronic Ticketing System (E-TLE) in Kulon Progo. Based on this, this research study aims to determine the increase in the performance of the police and the Ministry of Transportation in implementing e-tickets and solving cases of criminal acts of traffic violations. This type of research is field research, namely a form of research that aims to reveal the meaning given by society to their behavior and reality. The research method used is a qualitative method, which is a research approach that reveals certain social situations by describing reality correctly. The results of this study can be seen that the performance of the traffic police and the Ministry of Transportation in disseminating e-tickets includes explaining the procedure for measuring vehicle loads using weigh-in-motion (WIM). The data that can be obtained from this measurement is the total weight of the vehicle, the weight of the vehicle axle, the type of vehicle, the speed of the vehicle, and the distance between the vehicle axles has not been running in accordance with applicable and optimal procedures.